Transperitoneal and retroperitoneal approach in laparoscopic partial nephrectomy for posterior cT1 renal tumors: a retrospective, two-centers, comparative study - Ferakis, Nikolaos; Katsimantas, Antonios; Charalampogiannis, Nikos; Paparidis, Spyridon; Rassweiler, Jens; Gözen, Ali Serdar (Archivio italiano di urologia e andrologia, 2020)
Objectives: To compare perioperative, oncological and functional outcomes of Laparoscopic Transperitoneal Partial Nephrectomy (LTPN) and Retroperitoneal Laparoscopic Partial Nephrectomy (LRPN) for posterior, cT1 renal masses (RMs). Materials and methods: Databases of two urologic institutions applying different laparoscopic surgical approaches on posterior cT1 RMs between June 2016 and November 2018 were retrospectively evaluated. Data on patient demographics, perioperative data and tumor histology were collected and further analyzed statistically. Results: Each group consisted of 15 patients. Baseline characteristics were comparable in each group. When compared to LTPN, LRPN was associated with significantly shorter operative time (OT) (115 min versus 199 min, p < 0.05). No significant differences were detected in the other outcomes. Conclusions: LRPN is associated with a significantly shorter OT compared to LTPN for posterior cT1 RMs. Both surgical approaches are safe, feasible and credible, demonstrating optimal results.